2022
DOI: 10.1371/journal.pone.0269183
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of vaccine handlers and status of cold chain and vaccine management in primary health care facilities of Tigray region, Northern Ethiopia: Institutional based cross-sectional study

Abstract: Background Ethiopia federal ministry of health has been working on increasing access to immunization service by deploying solar refrigerators to primary health care facilities. However, there is limited evidence on cold chain and vaccine management status. Therefore, the objective of this study was to assess knowledge of vaccine handlers and status of cold chain and vaccine management and their associated factors in primary health care facilities of Tigray region Northern Ethiopia. Methods Institutional base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 18 publications
(62 reference statements)
4
12
7
Order By: Relevance
“…Also, most of the health workers (96.8%) knew the recommended temperature range for storage of routine vaccines (like Penta, Rota and PCV) at the health facility. These findings are consistent with the results of the studies conducted in Oromia, Ethiopia (96.9%) [7], Malaysia (95.5%) [14] and Tigray Ethiopia (80%) [15]. However, the results are higher than those reported in studies done in Bale and Gurage zone, Ethiopia (67.8% and 71.1%) [16,17], Cameroon (68.5%) [18], Mozambique (52%) [19] and Nigeria (52%) [20].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Also, most of the health workers (96.8%) knew the recommended temperature range for storage of routine vaccines (like Penta, Rota and PCV) at the health facility. These findings are consistent with the results of the studies conducted in Oromia, Ethiopia (96.9%) [7], Malaysia (95.5%) [14] and Tigray Ethiopia (80%) [15]. However, the results are higher than those reported in studies done in Bale and Gurage zone, Ethiopia (67.8% and 71.1%) [16,17], Cameroon (68.5%) [18], Mozambique (52%) [19] and Nigeria (52%) [20].…”
Section: Discussionsupporting
confidence: 92%
“…The findings from the study revealed that 79.3% had correct knowledge of the tool (vaccine vial monitor) that shows vaccine exposure to heat and 81.7% knew the discard points of the VVM stages. These results were found to be higher than those reported in other studies conducted in Tigray region, northern Ethiopia (64%) [15], Gojam zone, Ethiopia (58.3%) [22], Nigeria (45.3%) [20] and Ghana (38.1%) [1].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In Ethiopia, vaccine-preventable diseases are substantially contributing to under-five mortality. 8 The main problem in Ethiopia has been vaccines losing their potency during storage at the center, even if they were potent on arrival, which enhances the chances of several outbreaks from different parts of Ethiopia. 9 In addition according to reports from several findings in Ethiopia, the majority of facilities in Ethiopia have registered poor vaccine management practices and factors like EPI-related training, work experiences, and knowledge of cold chain management were reported as factors related to cold chain management practices.…”
Section: Introductionmentioning
confidence: 99%